Handlebar hernia - A rare complication from blunt trauma - So, Hang-Fai (Int J Surg Case Rep, 2018)
INTRODUCTION: Handlebar hernias are rare; they result from blunt force impacting the abdomen. This focal blunt trauma causes a tear of the underlying abdominal muscle and fascia without necessarily disrupting the skin. The site of the hernia is usually remote from the site of trauma so clinicians may be falsely reassured if they locally explore the site of bruising. The physical examination of such patient may not obviously suggest such an injury and the diagnosis can be easily missed. CASE PRESENTATION: A fit and well 10-year-old boy presented to the emergency department with left sided abdominal pain following a pushbike accident. He fell from his bicycle resulting in an impact of the handlebar to the left side of his abdomen. No obvious hernia was found on physical examination but there was a circular-shaped bruise in the left lower quadrant. An abdominal CT scan was then performed and the unusual diagnosis of a handlebar hernia was made. A prompt laparoscopic herniorrhaphy was performed and his post-operative recovery was uneventful. DISCUSSION: A high level of suspicion is required to diagnose handlebar hernias. Even relatively low-speed trauma can result in this insidious injury. Laparoscopic repair has been demonstrated to be successful in this case. CONCLUSION: Despite being a rare entity, handlebar hernias should be suspected when significant blunt force is applied to the abdominal wall from a handle bar injury. They may not be obvious on physical examination and therefore further imaging is often important. Management involves prompt surgical repair to prevent complications.